The Role of the Circle of Concerned African Women Theologians in Engendering Theological Higher Education in Africa - Naicker, Linda (Studia Historiae Ecclesiasticae, 2024)
This article explores the transformative role of the Circle of Concerned African Women Theologians in engendering higher theological education in Africa. Grounded in African Women’s theology, the study analyses initiatives in championing gender equality, inclusivity, and intersectional solidarity within theological academia. The study highlights the historic journey of the Circle of Concerned African Women Theologians in promoting the integration of gender-sensitive curricular and nurturing a new generation of African women theologians. Methodologically, I adopt a qualitative design and use African Women’s Theology as a lens to understand the transformative strides made by the Circle of Concerned African Women Theologians towards engendering theological higher education in Africa.
free
Keywords: Circle of Concerned African Women Theologians; Gender Equality; Higher Theological Education; the Circle; theological academia